Public wheat imports into Ethiopia since 2008: The rationales and cost-effectiveness - Rashid, Shahidur; Lemma, Solomon (International Food Policy Research Institute, 2014)
We note at the outset that, the main objective of this paper is to draw broad conclusions in order to guide discussions between the ATA management and the policy makers, not to present in depth analysis to answer each of these questions with equal depth of analytical rigor.